Drill Exercise Method Influences AbilityGroundstroke Tennis Court - Hendri Irawadi; M Jaqfaruhdin Yusuf (Performa, 2019)
Abstract: The problem in this study is the low ability of grounstroke students at the Faculty of Sport Science, Padang State University. This study aims to find out how much the groundstroke ability of students at the Faculty of Sports in Padang State University is using drill drill method. This type of research is quasi-experimental (quasi experimental). The population in this study were sports coaching students who took basic tennis tennis courses, while the sample was taken by random sampling with a total of 13 people. The instrument test used is the Hewitt Tennis Acheivement Test, one of which aims to evaluate the basic technique of a groundstroke. While the data analysis technique uses normality test and t-test. The results of this study are that there is an effect of the drill training method to increase the ability of FIK Groundstroke Students at Padang State University. This is proven by tcount = 3.41> t table = 1.77.